Urgensi Peran Swasta dalam Pengelolaan Pariwisata oleh Pemerintah Kabupaten Kotabaru Kalimantan Selatan - Qubayla, Farah; Hakim, Arif Rahman (Jurnal Noken: Ilmu-Ilmu Sosial, 2024)
This study aims to find out how the management of tourism and its obstacles by the Regional Government in Kotabaru Regency, South Kalimantan Province. This research is a descriptive qualitative research, with data collection methods through observation, interviews and literature study. The results of this study indicate that the Kotabaru Regency Government has made the tourism sector as one of the main visions of the region so that through the 2018-2025 Kotabaru Regency Tourism Development Master Plan, it is hoped that Kotabaru can become one of the leading tourist destinations in Indonesia as well as for the welfare of the community. However, in the management of its tourism, the Kotabaru Regency Government still facing one main obstacle, limited infrastructure. This obstacle can then be overcome not only by the local government, but also by the involvement of the local community and other stakeholders, especially the role of the private sector.